Equity financing in a banking crisis: Evidence from private firms - Federico Kochen (European Central Bank (ECB), 2025)
To what extent can private firms' external equity substitute for debt financing in a banking crisis? To answer this question, I use firm-level data and firm-bank linkages to estimate the causal effect of an imported lending cut from a large German bank on firms' capital structure and real outcomes. The estimates imply that for every 1 euro reduction in debt, private firms in Germany received 0.27 euros of external equity. Firm-owner linkages indicate that outsiders provided equity funds in 40% of the firms that received an equity injection, while existing owners provided the funds in the rest. These findings highlight the importance of multiple sources of financing that can serve as backup facilities when the primary source of intermediation fails. The results also have implications for Macro-Finance heterogeneous firm models that typically overlook the role of equity financing.
Keywords: G01; G21; G32; E32; E44; 330; equity financing; banking crisis; capital and ownership structure